GAMBARAN HASIL LABORATORIUM PASIEN COVID-19 YANG DIRAWAT DI RSUD ULIN BANJARMASIN PERIODE 2021-2022 - Maulidya, Andini Bena; Muthmainah, Noor; Skripsiana, Nika Sterina; Noor, Meitria Syahadatina; Rahmiati, Rahmiati (Homeostasis, 2024)
Abstract: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The purpose of this study was to determine the description of the laboratory results of COVID-19 patients treated at RSUD Ulin Banjarmasin in 2021-2022. This research was descriptive study by collecting data on medical records of COVID-19 sufferers who were treated and confirmed positive at the RSUD Ulin Banjarmasin for the 2021-2022 period and using a total sampling technique by taking the entire population. The results showed that in 2021 the abnormal laboratory results were segment neutrophilia (62,9%), trunk neutrophilia (99,9%), lymphopenia (57,8%), CRP increased (80,6%) and LDH increased (73,3%). Meanwhile in 2022 the abnormal laboratory results were anemia (71,5%), hemodilution (73,1%), erythropenia (54,9%), neutrophilia segment (60,1%), trunk neutrophilia (100%), lymphopenia (61,7%), CRP increased (73,9%) and LDH increased (70,4%). The average laboratory results for COVID-19 patients in 2021 were male hemoglobin (12,95 gr/dL), female hemoglobin (11,65 gr/dL), male hematocrit (38,73%), female hematocrit (35,38%), male erythrocytes (4,60 x 106 cells/mm3), female erythrocytes (4,22 x 106 cells/mm3), platelets (317.559 cells/mm3), leukocytes (11,250 cells/mm3), neutrophils (75.97%), lymphocytes (15,61%), CRP (58,10 mg/L), LDH (452,26 U/L). Meanwhile, the average in 2022 were male hemoglobin (11,40 gr/dL), female hemoglobin (11,65 gr/dL), male hematocrit (34,40%), female hematocrit (31,70%), male erythrocytes (4,10 x 106 cells/mm3), female erythrocytes (3,78 x 106 cells/mm3), platelets (321,652 cells/mm3), leukocytes (12.870 cells/mm3), neutrophils (75,37%), lymphocytes (14,52%), CRP (70,20 mg/L), LDH (402,36 U/L). The conclusion was that the transition period (2022) showed more variable abnormal laboratory results. Keywords: COVID-19, Laboratory Results, Infectious Disease Abstrak: Coronavirus Disease 2019 (COVID-19) merupakan penyakit menular yang disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Penelitian ini bertujuan untuk mengetahui gambaran hasil  laboratorium pasien COVID-19 yang dirawat di RSUD Ulin Banjarmasin periode 2021-2022. Penelitian ini merupakan penelitian deskriptif dengan pengambilan data rekam medis penderita COVID-19 yang dirawat dan terkonfirmasi positif di RSUD Ulin Banjarmasin periode 2021-2022 dan menggunakan teknik total sampling dengan cara mengambil seluruh populasi. Hasil penelitian menunjukkan bahwa pada tahun 2021 hasil laboratorium adalah yang abnormal neutrofilia segmen (62,9%), neutrofilia batang (99,9%), limfopenia (57,8%), CRP meningkat (80,6%) dan LDH meningkat (73,3%). Sedangkan tahun 2022 hasil yang abnormal laboratorium adalah anemia (71,5%), hemodilusi (73,1%), eritropenia (54,9%), neutrofilia segmen (60,1%), neutrofilia batang (100%), limfopenia (61,7%), CRP meningkat (73,9%) dan LDH meningkat (70,4%). Rerata hasil laboratorium pasien COVID-19 tahun 2021 yaitu hemoglobin laki-laki (12,95 gr/dL), hemoglobin perempuan (11,65 gr/dL), hematokrit laki-laki (38,73%), hematokrit perempuan (35,38%), eritrosit laki-laki (4,60 x 106 sel/mm3), eritrosit perempuan (4,22 x 106 sel/mm3), trombosit (317.559 sel/mm3), leukosit (11.250 sel/mm3), neutrofil (75,97%), limfosit (15,61%), CRP (58,10 mg/L), LDH (452,26 U/L). Sedangkan rerata tahun 2022 yaitu hemoglobin laki-laki (11,40 gr/dL), hemoglobin perempuan (11,65 gr/dL), hematokrit laki-laki (34,40%), hematokrit perempuan (31,70%), eritrosit laki-laki (4,10 x 106 sel/mm3), eritrosit perempuan (3,78 x 106 sel/mm3), trombosit (321.652 sel/mm3), leukosit (12.870 sel/mm3), neutrofil (75,37%), limfosit (14,52%), CRP (70,20 mg/L), LDH (402,36 U/L). Kesimpulannya adalah pada masa peralihan (2022) menunjukkan lebih banyak variabel hasil laboratorium yang abnormal. Kata-Kata kunci : COVID-19, Hasil Laboratorium, Penyakit Menular